Analisis Faktor-Faktor Kompleksitas Aplikasi Mobile Banking BCA terhadap User Experience Menggunakan UTAUT - Octavia, Debora; Tanaamah, Andeka Rocky (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2024)
In the present digital era, there has been a transformation in banking practices, moving away from traditional services towards those rooted in technology. Mobile Banking has become the primary means for users to conduct banking transactions. However, despite its prevalence, there are complexities in its usage that can affect user experience. This study proposes an analysis using the Technology Acceptance Model (TAM), specifically the Unified Theory of Acceptance and Use of Technology (UTAUT), to identify factors influencing the adoption of technology in BCA Mobile Banking. These factors include system complexity, lack of feature understanding, interface design issues in the application, and social barriers encountered during Mobile Banking usage. Through this study, it is anticipated that key factors affecting the adoption of Mobile Banking technology can be identified, enabling stakeholders to utilize this research as an assessment tool to enhance user experience and the efficiency of technology-based banking services.